ANALISA PENGARUH ARUS LISTRIK PENGELASAN GMAW ALUMUNIUM 5052 - Ariyanto Ariyanto (Jurnal Ilmiah Teknik, 2024)
Aluminum (Al) is a light metal that has corrosion resistance and good electrical conductivity. It is estimated that the use of aluminum in the future will still be wide open, both as a main material and as a supporting material, with the abundant availability of aluminum ore on earth. The welding process is one part of the manufacturing process. The welding process, which in principle is to connect two or more components, is more precisely indicated for assembling several components into a machine form. Welding Aluminum 5052 using GMAW welding with variations in welding electric current, namely 200A and 210 A, welding using the E4043 electrode. The aim of this research is to determine the strength of GMAW welded joints on Aluminum 5052 against the Charphy impact test. The GMAW welding electric current value at an electric current of 200 A produces a work force of 55.012 J and produces 0.678 J/????????2 impact charphy value, at an electric current of 210 A it produces a work force of 64.34 J and produces 0.804 J/????????2 impact charphy value. From the calculation results that have been obtained, the higher the GMAW welding electric current used causes the weld area to become more ductile, but on the contrary, the lower the GMAW welding electric current, the harder it is and tends to break easily.